Reactivity of the binuclear non-heme iron active site of Δ⁹ desaturase studied by large-scale multireference ab initio calculations - Chalupský, Jakub; Rokob, Tibor András; Kurashige, Yuki; Yanai, Takeshi; Solomon, Edward I; Rulíšek, Lubomír; Srnec, Martin (Journal of the American Chemical Society, 2014)
The results of density matrix renormalization group complete active space self-consistent field (DMRG-CASSCF) and second-order perturbation theory (DMRG-CASPT2) calculations are presented on various structural alternatives for the O-O and first C-H activating step of the catalytic cycle of the binuclear nonheme iron enzyme Δ(9) desaturase. This enzyme is capable of inserting a double bond into an alkyl chain by double hydrogen (H) atom abstraction using molecular O2. The reaction step studied here is presumably associated with the highest activation barrier along the full pathway; therefore, its quantitative assessment is of key importance to the understanding of the catalysis. The DMRG approach allows unprecedentedly large active spaces for the explicit correlation of electrons in the large part of the chemically important valence space, which is apparently conditio sine qua non for obtaining well-converged reaction energetics. The derived reaction mechanism involves protonation of the previously characterized 1,2-μ peroxy Fe(III)Fe(III) (P) intermediate to a 1,1-μ hydroperoxy species, which abstracts an H atom from the C10 site of the substrate. An Fe(IV)-oxo unit is generated concomitantly, supposedly capable of the second H atom abstraction from C9. In addition, several popular DFT functionals were compared to the computed DMRG-CASPT2 data. Notably, many of these show a preference for heterolytic C-H cleavage, erroneously predicting substrate hydroxylation. This study shows that, despite its limitations, DMRG-CASPT2 is a significant methodological advancement toward the accurate computational treatment of complex bioinorganic systems, such as those with the highly open-shell diiron active sites.
Keywords: Iron; Models, Molecular; termodynamika; železo; Quantum Theory; Stearoyl-CoA Desaturase; molekulární modely; katalytická doména; kvantová teorie; Thermodynamics; Catalytic Domain; stearyl-CoA-desaturasa